Laparoscopic Adrenalectomy in Elderly Patients. Issue 6 (December 2017) - Weinandt, Marthe; Gaujoux, Sébastien; Khayat, Antoine; Bertherat, Jérôme; Baillard, Christophe; Dousset, Bertrand
Abstract : With increase life expectancy, surgical indications in elderly become more frequent. The aim of this study was to analyze indications and outcome of laparoscopic adrenalectomy in patients over 75. Between 1994 and 2014, 641 patients underwent laparoscopic adrenalectomy. Preoperatively, all patients had a standardized preoperative work-up. Patients over 75 were compared with a control group of younger patients. The median age was 52 years (41 to 61) and 3.6% of patients (n=23) were over 75. Patients over 75 were more frequently operated for malignant lesion (21.7% vs. 4.7%; P =0.005). There was no postoperative mortality. Conversion rate was 3.4% (n=22), with no significant difference between the groups. The overall morbidity and severe morbidity rates were, respectively, 16.9% and 3.3%, with no significant difference between the groups. In experienced team and for selected patients, laparoscopic adrenalectomy after 75 years is safe, without increased postoperative morbidity, as compared with younger population.